Ultraviolet semiconductor light emitting element
The ultraviolet LED employs a codoped semiconductor structure with controlled impurity ratios to enhance efficiency, output, and reliability, addressing the rapid deterioration issue in conventional devices.
Patent Information
- Application Number
- JP2021072897
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-22
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2041-04-22
AI Technical Summary
Conventional ultraviolet semiconductor light emitting devices face challenges in achieving high efficiency, high output, and high reliability, particularly when driven with large currents, leading to rapid deterioration and short element life.
The device incorporates a specific semiconductor structure with an n-type AlGaN layer, an active layer, and a p-type AlY2Ga1-Y2N layer codoped with a p-type and n-type impurity, where the concentration ratio (Nd/Na) of n-type to p-type impurity is controlled within a specific range, and the p-type layer has a controlled impurity concentration to minimize nitrogen defects.
This structure results in an ultraviolet LED with high luminous efficiency, maintained output, and extended device life, overcoming the trade-off between efficiency and reliability.
Smart Images

Figure 0007604311000001 
Figure 0007604311000002 
Figure 0007604311000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an ultraviolet semiconductor light-emitting device, and more particularly to a nitride semiconductor light-emitting device that emits ultraviolet light. [Background technology]
[0002] In recent years, semiconductor light-emitting elements that emit light in the deep ultraviolet region have been attracting attention as light sources that have the effect of inactivating and sterilizing bacteria and viruses.
[0003] For example, Patent Document 1 discloses an AlGaN-based semiconductor light-emitting device in which a p-type semiconductor layer on an electron blocking layer is a compositionally graded layer.
[0004] Moreover, Patent Documents 2 and 3 disclose Group III nitride semiconductor light-emitting devices in which the electron blocking layer is doped with Si and Mg. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-160974 A [Patent Document 2] JP 2020-057783 A [Patent Document 3] JP 2019-083221 A Summary of the Invention [Problem to be solved by the invention]
[0006] In conventional ultraviolet semiconductor light-emitting devices, it was difficult to realize devices that were not only highly efficient and high-output, but also highly reliable. In particular, when driven with a large current to obtain high optical output, there was a problem that the device deteriorated early. In other words, it was difficult to achieve both high output characteristics and high reliability (long life).
[0007] The inventors of the present application have discovered a trade-off relationship and a degradation mechanism in which the higher the efficiency and output of an element, the greater the output drop after current is passed through it, and the shorter the element lifespan. The present invention has been made based on this discovery, and aims to provide an ultraviolet semiconductor light-emitting element that is highly efficient and high output, has little degradation, and has an excellent element lifespan. [Means for solving the problem]
[0008] An ultraviolet semiconductor light-emitting device according to one embodiment of the present invention comprises: n-type AlGaN layer, active layer, Al Y1 Ga 1-Y1 N layer (0.8≦Y1≦1.0) and p-type Al Y2 Ga 1-Y2 A semiconductor structure layer in which N layers (0.5≦Y2≦1.0, Y2≦Y1) are epitaxially grown in this order; The p-type Al Y2 Ga 1-Y2 the N layer is co-doped with a p-type impurity that serves as an acceptor and an n-type impurity that serves as a donor, and a concentration ratio (Nd / Na) of a concentration (Nd) of the n-type impurity to a concentration (Na) of the p-type impurity satisfies 0.009≦(Nd / Na)<0.185; The p-type Al Y2 Ga 1-Y2 The concentration of the p-type impurity in the N layer is 1×10 17 ~1.2×10 20 cm -3 and The Al Y1 Ga 1-Y1 The N layer does not contain the n-type impurity or the concentration of the n-type impurity is higher than that of the p-type Al Y2 Ga 1-Y2 The concentration of the n-type impurity in the N layer is less than that of the n-type impurity in the N layer. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view showing a schematic structure of an ultraviolet semiconductor light-emitting element 10 according to an embodiment of the present invention. [Diagram 2]1 is a diagram showing a schematic band diagram of an ultraviolet LED 10. FIG. [Diagram 3] 13 is a table showing the characteristics of the ultraviolet LEDs 10 obtained from two types of wafers having different Mg concentrations in the p-type AlY2Ga1-Y2N layer 15. [Figure 4A] 1 is a graph plotting the relationship between the Si concentration in a p-type AlY2Ga1-Y2N layer 15 and the luminous efficiency (arbitrary unit) at the beginning of current application. [Figure 4B] 1 is a graph plotting the relationship between the Si / Mg ratio (Si concentration / Mg concentration) of a p-type AlY2Ga1-Y2N layer 15 and the luminous efficiency (arbitrary unit) at the beginning of current application. [Figure 4C] 1 is a graph showing the output maintenance rate (@100h) after 100 hours have elapsed from the initial time versus the Si concentration in the p-type AlY2Ga1-Y2N layer 15. [Figure 4D] 1 is a graph showing the Si / Mg ratio (Si concentration / Mg concentration) of a p-type AlY2Ga1-Y2N layer 15 and the output maintenance ratio. [Diagram 5] 1 is a graph showing the output maintenance rate (@100h) versus the initial light output (arbitrary unit) at the start of energization for elements obtained from structures 1 and 2 (EX1 and EX2) and comparative examples 1 and 2 (CM1 and CM2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the following, preferred embodiments of the present invention will be described, which may be modified and combined as appropriate. In the following description and accompanying drawings, substantially the same or equivalent parts are designated by the same reference numerals.
[0011] [Structure of ultraviolet semiconductor light-emitting element] 1 is a cross-sectional view showing a schematic structure of an ultraviolet semiconductor light-emitting element 10 according to one embodiment of the present invention. The ultraviolet semiconductor light-emitting element 10 is an ultraviolet light-emitting diode (hereinafter referred to as an ultraviolet LED 10), and is formed by epitaxially growing an n-type AlGaN layer 12, an active layer 13, an AlGaN layer 14, a p-type AlGaN layer 15, and a p-type GaN layer 16 on a substrate 11 in that order.
[0012] 2 is a schematic diagram showing a band diagram of the ultraviolet LED 10. A more detailed description will be given with reference to FIGS.
[0013] The substrate 11 is preferably a substrate having a low dislocation density so that the dislocation density in the active layer is low, but is not particularly limited. 9 cm -2 Less than or equal to 10 8 cm -2 The materials listed below are preferred, and for example, an AlN template substrate having an AlN film laminated on a sapphire substrate as described in Patent Document 1 or a single crystal AlN substrate as described in Patent Document 2 can be used.
[0014] When using an AlN template substrate, the dislocation density at the top surface of the AlN layer must be 10 9 cm -2 More preferably, 10 8 cm -2 It is preferable to select the following: The method for growing the AlN layer on the template substrate is not particularly limited as long as the above-mentioned dislocation density is satisfied, and physical vapor deposition methods such as metalorganic chemical vapor deposition (MOCVD), hydride vapor phase epitaxy (HVPE), and sputtering can be used.
[0015] Furthermore, since a large surface roughness of the template substrate can cause abnormal growth of the AlGaN layer grown on the substrate, the surface roughness (RMS) is preferably 1.0 nm or less, and more preferably 0.5 nm or less. In order to obtain this surface roughness or to remove a damaged layer formed on the surface after growth, the surface of the template substrate may be polished by a known polishing method such as chemical mechanical polishing (CMP). A superlattice layer for interfering with the strain of the n-type AlGaN layer may also be provided on the AlN template substrate.
[0016] From the viewpoint of reducing the dislocation density in the active layer, it is preferable to use a single crystal AlN substrate as the substrate 11. The dislocation density of the single crystal AlN substrate is 10 8 cm -2 It is preferable that the value is 10 or less, and more preferably 10 6 cm -2 Below, most preferably 10 4 cm -2 The lower the dislocation density, the lower the 6 cm -2 Below, 10 4 cm -2 By using this AlN substrate, it is possible to prevent a decrease in the light-emitting efficiency in the active layer due to dislocations, and further to prevent problems such as the diffusion of impurities through dislocations and an increase in leakage current that occur when electricity is passed through the ultraviolet light-emitting element.
[0017] Furthermore, for the same reasons as those for the AlN template substrate described above, the surface roughness (RMS) of the single crystal AlN substrate 11 is preferably 1.0 nm or less, and more preferably 0.5 nm or less. Naturally, the surface of the AlN substrate may also be polished by a known polishing method such as chemical mechanical polishing (CMP).
[0018] In addition, if the absorption coefficient of the substrate for the ultraviolet light emitted from the active layer is large, the total amount of ultraviolet light that can be extracted to the outside is reduced, which may lead to a decrease in the light emission efficiency. Therefore, the absorption coefficient of the AlN substrate and the AlN layer of the AlN template is preferably 20 cm -1 Less than 10 cm, more preferably -1 Less than 10cm -1 By setting it to the following value, even if the thickness of the AlN substrate 11 is 100 μm, for example, it is possible to ensure an in-line transmittance of 90% or more.
[0019] The n-type AlGaN layer 12 is an n-type conductive layer doped with Si (silicon). The Al composition of the n-type AlGaN layer can be appropriately determined so as to obtain sufficient transparency for the desired emission wavelength of ultraviolet light. In the ultraviolet semiconductor light emitting device, ultraviolet light emitted from the light emitting layer passes through the n-type AlGaN layer 12 and the substrate 11 and is emitted to the outside. In addition, as the Al composition of the n-type AlGaN layer increases, the band gap of the n-type AlGaN layer increases, and accordingly, ultraviolet light of a shorter wavelength can be transmitted through the n-type AlGaN layer.
[0020] The n-type AlGaN layer 12 may be formed of a plurality of layers having different Al compositions, and may be a compositionally graded layer in which the Al composition is graded in the stacking direction. For example, the first n-type Al X1 Ga 1-X1 N layer 12A and second n-type Al X2 Ga 1-X2 The first n-type Al layer 12B X1 Ga 1-X1 The N layer 12A is a composition gradient layer in which the Al composition X1 decreases from 1.0 to 0.75 in the stacking direction. X2 Ga 1-X2 The N layer 12B may be a compositionally graded layer in which the Al composition X2 decreases from 0.75 to 0.70.
[0021] The thickness of the n-type AlGaN layer 12 is not particularly limited and is determined appropriately. When a single crystal AlN substrate is used for the substrate 11, the thickness of the n-type AlGaN layer 12 is preferably 0.5 μm or more and 2 μm or less. From the viewpoint of reducing the resistance value of the n-type AlGaN layer, a thicker n-type AlGaN layer is preferable, but when an AlN substrate is used for the substrate 11, if the n-type AlGaN layer is too thick, lattice relaxation occurs in the n-type AlGaN layer, which makes it more likely to generate dislocations.
[0022] For example, the n-type AlGaN layer 12 may be formed by the first n-type Al X1 Ga 1-X1 N layer 12A and second n-type Al X2 Ga 1-X2When the layer structure is formed from the N layer 12B, the first n-type Al X1 Ga 1-X1 The N layer 12A has a thickness of 200 nm and is a second n-type Al X2 Ga 1-X2 The N layer 12B may have a thickness of 1000 nm. X1 Ga 1-X1 N layer 12A and second n-type Al X2 Ga 1-X2 The thickness of N layer 12B is not limited to the exemplified values, and can be appropriately determined so that the total thickness is 2.0 μm or less.
[0023] On the other hand, when an AlN template substrate is used, the thickness of the n-type AlGaN layer 12 is preferably 1.5 μm or more and 10 μm or less. This is because a thicker n-type AlGaN layer 12 is expected to have the effect of reducing dislocations in addition to reducing the resistance value, and therefore a thickness of 1.5 μm or more is considered preferable. Also, when an AlN template substrate is used, the upper limit of the thickness of the n-type AlGaN layer 12 is considered to be about 10.0 μm in consideration of industrial viewpoints such as manufacturing time.
[0024] The Si concentration to be doped in the n-type AlGaN layer 12 may be appropriately determined so as to obtain a desired n-type conductivity. From the viewpoint of reducing the resistance value of the n-type AlGaN layer 12, however, it is preferable to set the Si concentration to 1×10 18 ~1×10 20 cm -3 It is preferable that the number of the particles is 5×10 18 ~5×10 19 cm -3 In addition, the Si doping concentration may be constant in the thickness direction in the n-type AlGaN layer, or it may be modulated doping in which the Si concentration varies in the thickness direction.
[0025] The Si concentration and the Mg concentration described below can be measured by known Secondary Ion Mass Spectrometry (SIMS) analysis. Also, the measured values of the Si concentration and the Mg concentration in the present application are quantitative values using standard samples of AlN, Al 0.65 Ga 0.35 N, and GaN for the AlN layer, the AlGaN layer, and the GaN layer, respectively.
[0026] The active layer (ACT) 13 is a quantum well structure composed of a barrier layer made of an Al A1 Ga 1-A1 N layer and a well layer made of an Al A2 Ga 1-A2 N layer. The emission peak wavelength of the active layer 13 is in the range of 210 to 300 nm. Since the wavelength of the light emitted from the active layer 13 is determined by the Al composition and the film thickness of the well layer, the Al composition and the film thickness can be appropriately determined so as to obtain a desired emission wavelength in the above wavelength range.
[0027] For example, the film thickness of the well layer can be set in the range of 2 to 10 nm, and the Al composition can be determined so as to obtain a desired emission wavelength. Also, the Al composition and the film thickness of the barrier layer are not particularly limited, but for example, the Al composition can be set in the range of A2 < A1 ≤ 1.0 and the film thickness can be set in the range of 2 to 15 nm.
[0028] Also, the well layer and the barrier layer can be n-type layers doped with Si. Both the well layer and the barrier layer may be Si-doping layers, or a structure in which only the well layer or only the barrier layer is doped with Si. The Si concentration to be doped is not particularly limited, but is preferably in the range of 1×10 17 ~5×10 18 cm -3 .
[0029] Also, the number of quantum well layers is not particularly limited, and it may be a multi-quantum well (MQW) structure in which a plurality of well layers are formed, or it may be a single quantum well (SQW). The number of well layers is preferably determined as appropriate within the range of 1 to 5.
[0030] Al Y1 Ga 1-Y1 The AlGaN layer 14 is a layer provided adjacent to the active layer 13. Y1 Ga 1-Y1 The AlGaN layer 14 functions as an electron blocking layer (EBL) for suppressing the overflow of electrons injected into the active layer 13 into the p-type AlGaN layer 15. Therefore, Y2 Ga 1-Y2 the AlGaN layer 14 has a larger bandgap than the active layer 13 and the p-type AlGaN layer 15 described later, and the Al composition Y1 of the AlGaN layer 14 is determined within the range of 0.8 < Y1 ≦ 1.0. Y1 Ga 1-Y1 As the emission wavelength becomes shorter, the Al composition of the AlGaN layer epitaxially grown on the substrate 11 increases. When the emission wavelength is shorter than 270 nm, in order to sufficiently exhibit the function as an electron blocking layer, it is preferable that 0.9 ≦ Y1 ≦ 1.0. In this embodiment, Y2 Ga 1-Y2 AlN (Y1 = 1) is used as the AlGaN layer 14. Y1 Ga 1-Y1 The AlGaN layer 14 may be an undoped layer or may be doped with a p-type dopant as long as it can exhibit the function as an electron blocking layer.
[0031] As the emission wavelength becomes shorter, the Al composition of the AlGaN layer epitaxially grown on the substrate 11 increases. When the emission wavelength is shorter than 270 nm, in order to sufficiently exhibit the function as an electron blocking layer, it is preferable that 0.9 ≦ Y1 ≦ 1.0. In this embodiment, Y1 Ga 1-Y1 AlN (Y1 = 1) is used as the AlGaN layer 14.
[0032] Also, Y1 Ga 1-Y1 the AlGaN layer 14 may be an undoped layer or may be doped with a p-type dopant as long as it can exhibit the function as an electron blocking layer. Y1 Ga 1-Y1Examples of p-type dopant materials that can be used in the N layer 14 include magnesium (Mg), zinc (Zn), beryllium (Be), and carbon (C). In particular, it is preferable to use Mg, which is generally used as a p-type dopant material for AlGaN layers, and Mg is also used in the examples of the present invention described below.
[0033] The p-type dopant material is Al Y1 Ga 1-Y1 The N layer 14 may be doped uniformly in the stacking direction, or the concentration of the dopant material may be changed in the stacking direction. For example, a stacked structure consisting of an undoped AlN layer 14A (Y1=1) and a Mg (magnesium)-doped p-type AlN layer 14B from the side in contact with the active layer may be used.
[0034] Al Y1 Ga 1-Y1 The p-type dopant concentration in the N layer 14 is not particularly limited, but in order to obtain the function as an electron blocking layer, it is preferable that the p-type dopant concentration is 5×10 18 ~1×10 20 cm -3 From the viewpoint of increasing the efficiency of carrier injection into the light-emitting layer, it is preferable that 19 ~8×10 19 cm -3 It is particularly preferred that:
[0035] The Al of the present invention Y1 Ga 1-Y1 The N layer 14 does not contain an n-type dopant or is a p-type Al Y2 Ga 1-Y2 The n-type dopant can be contained at a concentration lower than that of the n-type dopant contained in the N layer 15. Specifically, Al Y1 Ga 1-Y1 The n-type impurity concentration in the N layer 14 is 1×10 18 cm -3 According to the findings of the present inventors, p-type Al Y2 Ga 1-Y2 During the growth of the N layer 15, the adjacent Al Y1 Ga 1-Y1It is known that dopant diffusion occurs between the Al layer and the N layer 14. Y1 Ga 1-Y1 The concentration of n-type dopants in the N layer 14 is p-type Al Y2 Ga 1-Y2 If the N layer is higher than that of 15, Al Y1 Ga 1-Y1 p-type Al from N layer 14 Y2 Ga 1-Y2 The n-type dopant diffuses into the N layer 15, and the p-type Al Y2 Ga 1-Y2 It may be difficult to precisely control the n-type dopant concentration in the N layer 15. Y2 Ga 1-Y2 In order to prevent a change in the concentration of the n-type dopant in the N layer 15, at least Al Y1 Ga 1-Y1 The n-type dopant in the N layer 14 is p-type Al Y2 Ga 1-Y2 The concentration must be less than the concentration of the n-type dopant contained in the N layer 15 .
[0036] In addition, Al Y1 Ga 1-Y1 The thickness of the N layer 14 is determined based on its function as an electron blocking layer and its function as a p-type Al Y2 Ga 1-Y2 The thickness may be appropriately determined so that holes can be efficiently injected from the N layer 15 into the active layer, but is preferably in the range of 1 to 30 nm. If the thickness is less than 1 nm, electrons tunnel, which reduces the function as an electron blocking layer. On the other hand, if the thickness exceeds 30 nm, the p-type Al Y2 Ga 1-Y2 Holes are less likely to be injected into the active layer from the N layer 15. Y1 Ga 1-Y1 The thickness of the N layer 14 is preferably 2 to 20 nm, and more preferably 5 to 15 nm.
[0037] As mentioned above, Al Y1 Ga 1-Y1The Mg doped in the N layer 14 may have a concentration difference in the stacking direction. For example, an undoped AlN layer 14A may be stacked with a thickness of 1 to 5 nm on the side in contact with the active layer 13, and an Mg-doped p-type AlN layer 14B may be stacked with a thickness of 5 to 15 nm. In this case, the Mg doping concentration is 5×10 18 ~1×10 20 cm -3 Preferably, the concentration is 1×10 19 ~8×10 19 cm -3 It is particularly preferred that:
[0038] The p-type Al of the present invention Y2 Ga 1-Y2 The N layer 15 is made of the Al Y1 Ga 1-Y1 It is formed on the N layer 14 and functions as a p-type cladding layer. Y2 Ga 1-Y2 The N layer 15 is co-doped with p-type impurities that act as acceptors and n-type impurities that act as donors.
[0039] p-type Al Y2 Ga 1-Y2 Examples of p-type impurities that can be used for doping the N layer 15 include magnesium (Mg), zinc (Zn), beryllium (Be), and carbon (C). Of these, it is preferable to use Mg, which is generally used as a p-type dopant material for AlGaN semiconductors. Examples of n-type impurities that can be used include Si, germanium (Ge), selenium (Se), sulfur (S), and oxygen (O). Of these, it is preferable to use Si, which is generally used as an n-type dopant material.
[0040] The p-type Al of the present invention Y2 Ga 1-Y2 The N layer 15 is a p-type Al Y2 Ga 1-Y2 The ratio (Nd / Na) of the n-type impurity concentration (Nd) to the p-type impurity concentration in N layer 15 satisfies formula (1).
[0041] 0.009≦(Nd / Na)<0.185...Equation (1)
[0042] Furthermore, it is more preferable that Nd / Na satisfies any one of the following formulas.
[0043] 0.009≦(Nd / Na)<0.135...Equation (2) 0.038≦(Nd / Na)<0.185...Equation (3)
[0044] The p-type Al is selected so that Nd / Na satisfies any one of the above formulas (1) to (3). Y2 Ga 1-Y2 By co-doping the N layer 15, an ultraviolet LED having high luminous efficiency and good output maintenance rate (device life) is realized.
[0045] In addition, p-type Al Y2 Ga 1-Y2 The amount of p-type impurities doped into the N layer 15 is 1×10 17 ~1.2×10 20 cm -3 As theoretically shown in J. Appl. Phys. 95, No. 8, 15 April (2004), p-type Al Y2 Ga 1-Y2 It is believed that the amount of nitrogen defects, which is considered to be a cause of deterioration, increases with the amount of p-type impurities in the N layer 15. 20 cm -3 If it exceeds this value, the amount of nitrogen defects formed in the initial stage becomes too large, making it difficult to obtain a high output maintenance rate.
[0046] Furthermore, when the p-type impurity concentration is low, particularly when the Al composition Y2 is constant, the hole concentration decreases and the minority carrier (electron) mobility increases, and when the Al composition Y2 is inclined, the minority carrier (electron) mobility increases, causing a decrease in output and making it difficult to obtain high luminous efficiency. Therefore, the p-type impurity concentration can be appropriately determined within the above range, taking such a trade-off into consideration, but in order to obtain a higher output maintenance rate and high output, it is recommended to set the p-type impurity concentration to 1×10 19 ~5×10 19 cm-3 More preferably, it is 1×10 19 ~4×10 19 cm -3 It is.
[0047] p-type Al Y2 Ga 1-Y2 The amount of n-type impurities doped into the N layer 15 is 1.1×10 18 Above 9.0×10 18 cm -3 It is preferable that the number of the particles is 1.8×10 or less, and more preferably, 1.8×10 18 Above 8.0×10 18 cm -3 With these amounts of n-type impurities, a light emitting device 10 with high luminous efficiency can be obtained.
[0048] In addition, p-type Al Y2 Ga 1-Y2 The p-type impurity and n-type impurity doped in the N layer 15 may have a constant concentration within the layer, or may have a concentration difference in the stacking direction. For example, Al Y1 Ga 1-Y1 The side in contact with the N layer 14 is a co-doped layer, and the remaining p-type Al Y2 Ga 1-Y2 The N layer 15 may be a layer that is not doped with n-type impurities.
[0049] p-type Al Y2 Ga 1-Y2 The Al composition Y2 of the N layer 15 is 0.5 or more and 1.0 or less, and Al Y1 Ga 1-Y1 The Al composition of the N layer 14 is equal to or less than Y1.
[0050] p-type Al Y2 Ga 1-Y2 In the case of a structure in which Y2 is a constant value in the stacking direction, the Al composition Y2 of the N layer 15 exceeds the Al composition of the barrier layer of the active layer and is Y1 Ga 1-Y1 The Al composition of the N layer 14 is preferably equal to or less than Y1. Y2 Ga 1-Y2By setting the Al composition Y2 of the N layer 15 in the above range, a high carrier overflow suppression effect can be obtained even when the amount of injected current of the ultraviolet light emitting device is large. In order to obtain a higher effect, the Al composition of the barrier layer of the active layer and the p-type Al Y2 Ga 1-Y2 It is preferable that the difference in the Al composition Y2 of the N layer 15 is 0.5 or more. Y2 Ga 1-Y2 The Al composition Y2 of the N layer 15 is preferably larger than the Al composition of the n-type AlGaN layer 12, which enhances the effect of suppressing carrier overflow to the p-type layer and improves the light emission efficiency of the ultraviolet light emitting device. Y2 Ga 1-Y2 In the case of a structure in which Y2 is a constant value in the stacking direction, the Al composition Y2 of the N layer 15 is preferably 0.6 or more and 0.9 or less.
[0051] In addition, p-type Al Y2 Ga 1-Y2 The N layer 15 may be a compositionally graded layer in which the Al composition Y2 changes in the stacking direction. Y1 Ga 1-Y1 It is preferable that the Al composition Y2 decreases in the stacking direction from the side in contact with the N layer 14. Y2 Ga 1-Y2 Since a polarization doping effect is obtained in the N layer 15, a higher hole concentration is easily obtained, and as a result, the efficiency of hole injection into the active layer is increased. For example, when the emission wavelength is 270 nm or less, Al Y1 Ga 1-Y1 The Al composition on the side in contact with the N layer 14 is preferably 0.95 to 1.0, and the p-type Al Y2 Ga 1-Y2 The Al composition in the surface layer of the N layer 15 is preferably 0.60 to 0.85. By employing such a structure, the above-mentioned polarization doping effect can be enhanced and transparency to the emission wavelength can be maintained, making it easier to obtain high luminous efficiency.
[0052] In addition, p-type Al Y2 Ga 1-Y2The thickness of the N layer 15 is not particularly limited, but may be appropriately determined within the range of 10 to 150 nm. Y2 Ga 1-Y2 If the thickness of the N layer 15 is less than 10 nm, it becomes difficult to obtain the above-mentioned effect of suppressing carrier overflow. On the other hand, if the thickness is too thick and exceeds 150 nm, the p-type Al Y2 Ga 1-Y2 The resistance value of the N layer 15 increases, resulting in an increase in the operating voltage of the ultraviolet light emitting device. Y2 Ga 1-Y2 The thickness of the N layer 15 is preferably 40 to 120 nm, and particularly preferably 50 to 100 nm.
[0053] p-type Al Y2 Ga 1-Y2 On the N layer 15, a p-type GaN layer 16 doped with a p-type dopant may be formed in order to reduce the contact resistance with the electrode. The above-mentioned known p-type dopant materials can be used as the p-type dopant material, but for the same reason, it is preferable to use Mg. The Mg doping concentration in the p-type GaN layer 16 is not particularly limited, but in order to reduce the resistance value in the p-type GaN layer and the contact resistance with the electrode, it is preferable to use a concentration of Mg of 1×10 18 ~2×10 20 cm -3 In addition, the thickness of the p-type GaN layer 16 is not particularly limited, and may be appropriately determined within the range of 5 to 500 nm.
[0054] When AlN is used as the substrate 11, all layers of the AlGaN layers 12, 13, 14, and 15, except for the p-type GaN layer 16, are grown in a state of lattice bonding with the AlN substrate 11, and therefore have a low dislocation density equivalent to that of the AlN substrate 11. 5 cm -2 The dislocation density is as follows:
[0055] Although the ultraviolet semiconductor light emitting element 10 has been described as a light emitting diode (LED), it may be configured as a semiconductor laser element (LD: Laser Diode).
[0056] Although the ultraviolet semiconductor light emitting element 10 has been described as a semiconductor light emitting element having a substrate 11, the substrate 11 can be removed as necessary or can be provided arbitrarily depending on the properties of the substrate used.
[0057] Although the ultraviolet semiconductor light emitting element 10 has been described as a semiconductor light emitting element having a substrate 11 on the n-type AlGaN layer 12 side, a support substrate other than the substrate 11 used for epitaxial growth may be provided on the p-type GaN layer 16 side. In this case, the material of the support substrate is not particularly limited, and any known material used as a support substrate member for a light emitting element, such as polycrystalline AlN, Si, Al2O3Cu, CuW, etc., may be used without any restrictions.
[0058] In the following, as the ultraviolet semiconductor light-emitting element 10, a semiconductor light-emitting element having a substrate 11 as a growth substrate of a semiconductor laminate structure will be described. However, as described above, the semiconductor light-emitting element may also have a substrate 11 that is different from a growth substrate such as a support substrate.
[0059] Next, a method for manufacturing an ultraviolet LED having the structure described above will be described. The ultraviolet LED 10 of the present invention can be manufactured by known crystal growth methods such as MOCVD and molecular beam epitaxy (MBE). Among them, the MOCVD method is preferred because it has high productivity and is widely used industrially. The Group III (Al, Ga) source gas and Group V (N) source gas used in the present invention can be any known source gas without any particular restrictions.
[0060] For example, the Group III source gas may be trimethylaluminum, triethylaluminum, trimethylgallium, triethylgallium, etc. The Group V source gas is usually ammonia.
[0061] Furthermore, as the dopant source gas for Mg and Si, known materials can be used without any restrictions, such as biscyclopentadienyl magnesium, monosilane, and tetraethylsilane.
[0062] The above-mentioned source gases are supplied onto the substrate 11 together with a carrier gas such as hydrogen and / or nitrogen to grow the element layers of the ultraviolet LED 10.
[0063] The supply ratio of the Group III source gas to the Group V source gas (V / III ratio) may be appropriately determined so as to obtain desired characteristics, but is preferably set within the range of 500 to 10,000.
[0064] The growth temperature of the element layers constituting the ultraviolet LED 10 is not particularly limited and may be appropriately determined so as to obtain the desired characteristics of each layer and the characteristics of the ultraviolet LED 10. However, growth at a temperature of 1000 to 1200°C is preferable, and 1000 to 1150°C is more preferable. EXAMPLES
[0065] Hereinafter, the present invention will be specifically described using an example in which an ultraviolet LED with an emission wavelength of 265 nm was fabricated, but the present invention is not limited to the example.
[0066] [Fabrication of element] The substrate on which the UV-LED element layer was grown was an AlN single crystal substrate fabricated by the method described in Applied Physics Express 5 (2012) 122101. Specifically, it was a laminated substrate with a C-plane AlN seed substrate fabricated by physical vapor transport (PVT) and an AlN thick film grown by HVPE. The dislocation density of this AlN substrate was 10 5 cm -2 Less than or equal to 5 x 5 μm 2 The surface roughness (RMS) in the range was 0.1 nm.
[0067] On this AlN substrate, an AlN layer (100 nm), a first n-type AlGaN layer 12A (200 nm), and a second n-type AlGaN layer 12B (1000 nm) were grown by MOCVD equipment. The first n-type AlGaN layer 12A and the second n-type AlGaN layer 12B are both compositionally graded layers, with the Al composition decreasing from 1.0 to 0.75 from the side in contact with the AlN layer in the first n-type AlGaN layer 12A, and the Al composition decreasing from 0.75 to 0.70 from the side in contact with the first n-type AlGaN layer 12A in the second n-type AlGaN layer 12B. The Si concentration in the n-type AlGaN layer 12 was 1×10 19 cm -3 The control was performed so that
[0068] Next, n-type Al 0.6 Ga 0.4 A barrier layer of N (7 nm) and Al 0.5 Ga 0.5 The active layer 13 was grown as a triple quantum well layer consisting of a well layer of N (4 nm). The Si concentration of the barrier layer was 1×10 18 cm -3 The control was performed so that
[0069] Next, the electron blocking layer 14 made of AlN (10 nm) was grown. The electron blocking layer on the side in contact with the barrier layer was an undoped layer 14A (2 nm), and the remaining electron blocking layer 14B was a 4×10 19 cm -3 The undoped AlN layer 14A and the Mg-doped p-type AlN layer 14B were not doped with Si.
[0070] Next, a p-type AlGaN layer 15 (60 nm) was grown. The p-type AlGaN layer 15 is a compositionally graded layer in which the Al composition decreases from 1.0 to 0.8 from the side in contact with the electron blocking layer. The Mg concentration of the p-type AlGaN layer 15 is 1.0×10 20 cm -3 (Hereafter, 1.0E20cm -3 The Mg concentration of the p-type AlGaN layer 15 is 4.3E19 cm -3In each structure, the Si concentration for co-doping was set to 1×10 18 ~9×10 18 cm -3 A number of wafers were fabricated with the adjustment in the range.
[0071] Next, a p-type GaN layer 16 (270 nm) was grown to complete the deep ultraviolet LED element layer. The Mg concentration in the p-type GaN layer 16 was 5×10 19 cm -3 It was decided.
[0072] Next, the second n-type AlGaN layer was etched by ICP (inductively coupled plasma) dry etching until it was exposed, and then an n-type electrode was formed by laminating a Ti layer and a Au layer, and heat treatment was performed in a nitrogen atmosphere at 900°C. Next, a p-electrode was formed by laminating a Ni layer and a Au layer on the p-type GaN layer, and heat treatment was performed in an oxygen atmosphere at 500°C.
[0073] Next, the back side of the growth substrate (the side opposite to the UV-LED element layer) was mechanically polished until the AlN thick film formed by the HVPE method was exposed, completing the UV-LED. Next, the substrate was cut into chips of 0.75 mm x 0.95 mm by dicing, and then flip-chip bonded onto a ceramic submount to complete the UV-LED element.
[0074] FIG. 3 is a table showing the Mg concentration, Si concentration, and the ratio of the Si and Mg concentrations (Si / Mg) in the p-type AlN layer 14 and the p-type AlGaN layer 15.
[0075] In addition, wafers not co-doped with Si were also produced as Comparative Examples 1 and 2 (hereinafter referred to as CM1 and CM2) for Structure 1 (EX1) and Structure 2 (EX2). The Mg concentration of the p-type AlGaN layer 15 of the wafers CM1 and CM2 was 1.0E20 cm -3 , 4.3E19cm -3This is the same as the wafers of structure 1 (EX1) and structure 2 (EX2). Note that Si is also incorporated in the structure of the comparative example without co-doping, and SIMS (Secondary Ion Mass Spectrometry) measurement revealed that the Si concentration was 7×10 16 ~1×10 17 cm -3 Although about 7 × 10 Si was detected, this represents the detection limit in SIMS analysis, and the actual concentration is much lower. 16 ~1×10 17 cm -3 The degree indicates that the concentration is not greater than this.
[0076] [Element evaluation] The Mg concentration, Si concentration and light emission characteristics of the various ultraviolet LEDs 10 described above were evaluated. The Mg concentration and Si concentration were measured by SIMS measurement for each element. For the quantification of the AlN layer and the AlGaN layer, AlN, Al 0.65 Ga 0.35 N was used, respectively.
[0077] (1) Initial luminous efficiency FIG. 4A shows p-type Al Y2 Ga 1-Y2 1 is a graph plotting the relationship between the Si concentration in the N layer 15 (hereinafter also referred to as the p-type cladding layer 15) and the luminous efficiency (arbitrary unit) at the beginning of current application. In both Structure 1 and Structure 2, the initial luminous efficiency was hardly changed or only slightly decreased by co-doping with Si. However, in Structure 1, when the Si concentration was 8E18 cm -3 The luminous efficiency drops sharply when the Si concentration is increased to 9E18 cm -3 When the luminous efficiency was increased to , the luminous efficiency decreased rapidly.
[0078] FIG. 4B shows p-type Al Y2 Ga 1-Y21 is a graph plotting the relationship between the Si / Mg ratio (Si concentration / Mg concentration) of N layer 15 and the luminous efficiency (arbitrary unit) at the beginning of current flow. In structure 1, the luminous efficiency decreased rapidly when the Si / Mg ratio became 0.135 or more, and in structure 2, the luminous efficiency decreased rapidly when the Si / Mg ratio became 0.185 or more.
[0079] That is, p-type Al Y2 Ga 1-Y2 The Si concentration of the N layer 15 is 9E18 cm -3 It is preferable that the thickness is less than 8E18cm. -3 It was found that it is more preferable that the p-type Al Y2 Ga 1-Y2 It was found that the Si / Mg ratio of the N layer 15 is preferably less than 0.185, and more preferably less than 0.135.
[0080] (2) Output maintenance rate 4C is a graph showing the output maintenance rate (@100h) after 100 hours from the initial time versus the Si concentration of the p-type cladding layer 15. More specifically, the output maintenance rate, which is the rate of change in element output after 100 hours (hr) of current flow to the element from the start of current flow to the element, is plotted versus the Si concentration of the p-type cladding layer 15. Note that current was passed through the element in a constant current (ACC) drive mode in which a drive current of 450 mA was passed through the element.
[0081] 4D is a graph showing the output maintenance ratio and the Si / Mg ratio (Si concentration / Mg concentration) of the p-type cladding layer 15. In both the case of Structure 1 (EX1) and Structure 2 (EX2), the output maintenance ratio shows a tendency to improve as the Si concentration and Si / Mg ratio of the p-type cladding layer 15 increase.
[0082] (Structure 1:EX1) Regarding the Si concentration, referring to FIG. 4C and FIG. 3, the structure 1 in which the Mg concentration of the p-type cladding layer 15 is high (EX1: 1.0E20 cm -3 ) when the Si concentration is 1.1E18cm -3 The output maintenance rate has improved. In addition, the Si concentration is 9.0E18cm-3 If it was below this level, there would be no reduction in output.
[0083] 4D and 3, the output maintenance rate improved when the Si / Mg ratio was 0.009 or more, and no output reduction occurred when the Si / Mg ratio was less than 0.135.
[0084] (Structure 2:EX2) Regarding the Si concentration, referring to FIG. 4C and FIG. 3, the Mg concentration in the p-type cladding layer 15 of the structure 2 (EX2: 4.3E19 cm -3 ) when the Si concentration is 1.8E18cm -3 The output maintenance rate has improved. In addition, the Si concentration is 8.0E18cm -3 If it was below this level, there would be no reduction in output.
[0085] 4D and 3, the output maintenance rate improved when the Si / Mg ratio was 0.038 or more. Also, when the Si / Mg ratio was less than 0.185, no output reduction occurred.
[0086] (Si / Mg ratio) As shown in Fig. 4D, in both Structure 1 and Structure 2, the power retention ratio increases almost linearly with increasing Si / Mg ratio, and the Si / Mg ratio is considered to be the dominant physical parameter that governs the power retention ratio. The Si / Mg ratio is estimated to be inversely proportional to the concentration of nitrogen defects formed in the undoped state.
[0087] Specifically, when the Si / Mg ratio is 0.009 or more, 0.038 or more, or 0.064 or more, the output maintenance ratio is expected to be 0.7 or more, 0.8 or more, or 0.9 or more, respectively.
[0088] Even when Si is not co-doped (CM1 (Comparative Example 1) and CM2 (Comparative Example 2)), Comparative Example 2 (CM2) with a low Mg concentration shows a higher output maintenance ratio. This is thought to be because, as will be described later (FIG. 5), in Structure 1 and Comparative Example 1 with a high Mg concentration, the initial value of the nitrogen vacancy concentration, which is considered to be the true cause of degradation, is large.
[0089] Therefore, by co-doping the p-type cladding layer 15 so that the Si / Mg ratio satisfies the following formula, an ultraviolet LED having high luminous efficiency and good output maintenance rate (device life) is realized.
[0090] 0.009≦(Si / Mg)<0.185...Equation (1)
[0091] It is more preferable that the Si / Mg ratio satisfies any one of the following formulas.
[0092] 0.009≦(Si / Mg)<0.135...Equation (2) 0.038≦(Si / Mg)<0.185...Equation (3)
[0093] (Initial output and output maintenance rate) FIG. 5 is a graph showing the output maintenance rate (@100h) versus the initial light output (arbitrary units) at the start of current application for elements obtained from Structure 1 (EX1), Structure 2 (EX2), Comparative Example 1 (CM1), and Comparative Example 2 (CM2).
[0094] In the devices of Comparative Examples 1 and 2 (CM1 and CM2), the output maintenance rate was low at the beginning of current application (up to 100 h) in the reliability test, and the decrease in light output was large. In addition, there is a trade-off relationship in which the higher the efficiency (i.e., the higher the output), the larger the output decrease, making it difficult to fabricate a device with both high output and high reliability.
[0095] On the other hand, in the elements of the structures 1 and 2 (EX1, EX2) of the present invention, the output maintenance ratio is large at the beginning of charging (up to 100 h), and it is found that the decrease in the optical output is suppressed. Also, the structure 2 (EX2) having a low Mg concentration in the p-type cladding layer 15 has a higher output maintenance ratio than the structure 1 (EX1).
[0096] It was confirmed that the output maintenance rate (@100h) correlates with the long-term life (1000h). Therefore, it was confirmed that the elements of structures 1 and 2 (EX1, EX2) are also superior in terms of long-term life, and according to the present invention, it is possible to realize an element that is highly efficient, has high output, and is highly reliable.
[0097] [Estimation of the cause of deterioration] It has been reported that the general cause of output reduction in ultraviolet LEDs is degradation of the active layer, that is, an increase in point defects in the active layer, which reduces the recombination probability (probability of luminescence transition). Based on the above findings and the results of verification experiments carried out in the process of completing the present invention, the inventors have come to deduce the following mechanism of deterioration of UV LEDs. Y2 Ga 1-Y2 By doping the N layer 15 with Si, which acts as a donor, p-type Al Y2 Ga 1-Y2 It is presumed that the nitrogen defects in the N layer 15 are reduced. As a result, the amount of nitrogen defects diffusing into the active layer is reduced, which is presumed to suppress deterioration of the active layer and result in a high output maintenance rate.
[0098] (co-doped impurities) In the above embodiment, the p-type cladding layer is p-type Al Y2 Ga 1-Y2 Although the case has been described where Mg is used as the p-type impurity in N layer 15 and Si is used as the co-doped impurity, the present invention is not limited to this.
[0099] As described above, the mechanism of the present invention is p-type Al Y2 Ga 1-Y2It is believed that the effect of reducing nitrogen defects is due to the interaction between Mg, which is an acceptor impurity doped into the N layer 15, and Si, which is a donor impurity. Y2 Ga 1-Y2 Any material can be used without any restrictions as long as it functions as an acceptor and a donor for the N layer 15 .
[0100] Specifically, Zn (zinc), Be (beryllium), C (carbon), etc. can be used as p-type impurities acting as acceptors other than Mg. Also, Ge (germanium), Se (selenium), S (sulfur), O (oxygen), etc. can be used as n-type impurities (co-doped impurities) acting as donors other than Si.
[0101] Therefore, in general, p-type Al Y2 Ga 1-Y2 When the p-type impurity concentration of N layer 15 is Na and the n-type impurity concentration is Nd, it is preferable that Nd / Na satisfies the following formula.
[0102] 0.009≦(Nd / Na)<0.185...Equation (4)
[0103] It is more preferable that Nd / Na satisfies any one of the following formulas.
[0104] 0.009≦(Nd / Na)<0.135...Equation (5) 0.038≦(Nd / Na)<0.185...Equation (6)
[0105] Therefore, by co-doping the p-type cladding layer 15 with Nd / Na so as to satisfy the above formula, an ultraviolet LED having high luminous efficiency and good output maintenance rate (device life) is realized.
[0106] As described above in detail, according to this embodiment, it is possible to provide an ultraviolet LED that is highly efficient, has a high output, is less prone to deterioration, and has an excellent element lifespan. [Explanation of symbols]
[0107] 10: ultraviolet semiconductor light emitting element, 11: substrate, 12: n-type AlGaN layer, 12A: first n-type Al X1 Ga 1-X1 N layer, 12B: second n-type Al X2 Ga 1-X2 N layer, 13: active layer, 14: Al Y1 Ga 1-Y1 N layer, 14A: AlN layer, 14B: p-type AlN layer, 15: p-type AlGaN layer, 16: p-type GaN layer
Claims
1. n-type AlGaN layer, active layer, Al Y1 G 1-Y1 N layer (0.8≦Y1≦1.0) and p-type Al Y2 G 1-Y2 a semiconductor structure layer in which N layers (0.5≦Y2≦1.0, Y2≦Y1) are epitaxially grown in this order; The p-type Al Y2 G 1-Y2 the N layer is co-doped with a p-type impurity that serves as an acceptor and an n-type impurity that serves as a donor, and a concentration ratio (Nd / Na) of a concentration (Nd) of the n-type impurity to a concentration (Na) of the p-type impurity satisfies 0.009≦(Nd / Na)<0.185; the p-type impurity concentration of the p-type Al Y2 Ga 1-Y2 N layer is 1×10 17 to 1.2×10 20 cm −3 , The Al Y1 G 1-Y1 The N layer does not contain the n-type impurity or the concentration of the n-type impurity is higher than that of the p-type Al Y2 G 1-Y2 the concentration of the n-type impurity in the N-layer is less than that in the N-layer.
2. 2. The ultraviolet semiconductor light emitting element according to claim 1, wherein the p-type impurity is Mg (magnesium) and the n-type impurity is Si (silicon).
3. 3. The ultraviolet semiconductor light emitting element according to claim 2, wherein a concentration ratio of the n-type impurity to the p-type impurity, Si / Mg, satisfies 0.009≦(Si / Mg)<0.
135.
4. 3. The ultraviolet semiconductor light emitting element according to claim 2, wherein the concentration ratio satisfies 0.038≦(Si / Mg)<0.
185.
5. The Al Y1 G 1-Y1 5. The ultraviolet semiconductor light emitting element according to claim 1, wherein the N layer contains Mg as an impurity.
6. The p-type Al Y2 G 1-Y2 The N layer is the Al Y1 G 1-Y1 6. The ultraviolet semiconductor light emitting element according to claim 1, which is a composition gradient layer in which the Al composition decreases with increasing distance from the N layer.
7. The Al Y1 G 1-Y1 7. The ultraviolet semiconductor light-emitting element according to claim 1, wherein the N layer includes an undoped layer formed on the active layer, and an Mg-doped layer formed on the undoped layer.
8. The Al Y1 G 1-Y1 8. The ultraviolet semiconductor light-emitting element according to claim 1, wherein the N layer is an AlN layer.
9. The semiconductor structure layer is formed on a substrate, 9. The ultraviolet semiconductor light-emitting device according to claim 1, wherein the substrate is a single crystal AlN substrate.
Citation Information
Patent Citations
Semiconductor light-emitting element
JP2000208814A
Group iii nitride semiconductor light emitting element and manufacturing method of the same
JP2018093160A
Nitride semiconductor light-emitting element and method for manufacturing the same
JP2019083221A
Semiconductor light-emitting element
JP2019160974A
Imprint mold substrate, imprint mold, and manufacturing method thereof
JP2020057783A
